2020
DOI: 10.1177/0963947020936013
|View full text |Cite
|
Sign up to set email alerts
|

Real readers reading Wasco’s ‘City’: A storyworld possible selves approach

Abstract: This study empirically investigates reader responses to the one-page graphic narrative ‘City’ within the theoretical framework of storyworld possible selves. These are blended structures resulting from the conceptual integration of two input spaces: the mental representation that readers construct for the narrator or character that perspectivizes a narrative, and the mental representation that readers entertain for themselves, or self-concept. In our study, we use a questionnaire to elicit information about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…If one were to test all its networked components at once and on both levels of text and reader, accounting for the high variability across different readers, they may easily fail to generalize any result beyond the one tested text stimulus. Indeed, the only empirical investigation carried out with an SPS framework so far is a small-scale qualitative study that investigated readers' SPSs within their interpretation of a text-less, one-page graphic narrative (Martínez & Herman, 2020).…”
Section: Storyworld Possible Selvesmentioning
confidence: 99%
“…If one were to test all its networked components at once and on both levels of text and reader, accounting for the high variability across different readers, they may easily fail to generalize any result beyond the one tested text stimulus. Indeed, the only empirical investigation carried out with an SPS framework so far is a small-scale qualitative study that investigated readers' SPSs within their interpretation of a text-less, one-page graphic narrative (Martínez & Herman, 2020).…”
Section: Storyworld Possible Selvesmentioning
confidence: 99%
“…However, others are totally unpredictable and idiosyncratic, depending on individual readers' personal experience and even personality (Holland 1975(Holland , 2009. Storyworld possible selves can thus serve to account for both idiosyncratic and culturally predictable narrative meaning construction (Martinez/Herman, 2020).…”
Section: Storyworld Possible Selvesmentioning
confidence: 99%
“…[4] the fact that the majority of readers do not want to change their first self -interpretation when rea din g a literary work [5]. Reader empathy [6] and features of the work's visual perception [7] are important consideratio n. T h e reader's emotional response to the graphic narrative [8] and psychological projection in relation to emotion and discourse [9]. Moderation of readers and online reading [10] of text and reader factors Critical studies such as, empathic experience in complex communicatio n [11] have shown a number of features of perception and understanding of the text of a literary work.…”
Section: Introductionmentioning
confidence: 99%